2017
DOI: 10.1104/pp.16.01750
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrofolate Modulates Floral Transition through Epigenetic Silencing

Abstract: Folates, termed from tetrahydrofolate (THF) and its derivatives, function as coenzymes in one-carbon transfer reactions and play a central role in synthesis of nucleotides and amino acids. Dysfunction of cellular folate metabolism leads to serious defects in plant development; however, the molecular mechanisms of folate-mediated cellular modifications and physiological responses in plants are still largely unclear. Here, we reported that THF controls flowering time by adjusting DNA methylation-regulated gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
8
0
1
Order By: Relevance
“…Numerous studies have reported the regulation mechanism of owering process in their whole life cycle of plants, including oral induction [37], juvenile-to-adult transition [38], reproduction [12], and oral organ identity process [39] involved in transcriptional and post-transcriptional, and epigenetic regulation in multiple owering pathways. DNA methylation as epigenetic modi cations regulation is critical for oral induction and formation in woody plants, such as Apple [3], Pear [16], and Citrus [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the regulation mechanism of owering process in their whole life cycle of plants, including oral induction [37], juvenile-to-adult transition [38], reproduction [12], and oral organ identity process [39] involved in transcriptional and post-transcriptional, and epigenetic regulation in multiple owering pathways. DNA methylation as epigenetic modi cations regulation is critical for oral induction and formation in woody plants, such as Apple [3], Pear [16], and Citrus [18].…”
Section: Discussionmentioning
confidence: 99%
“…3). Indeed, the DMRs happened on various genomic regions (i.e., promoter, gene-body, or intron) may lead to different gene transcript levels in multiple plants [3,37], indicating that gene transcription is closely related to methylation. In our data, we found that methylation levels had a negative regulatory relationship with gene expression levels involved in the CG, CHG, and CHH contexts in the gene-body region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that in Arabidopsis, high folate levels delay inflorescence initiation (Wang et al, 2017), we examined whether the trifoliate mutation influenced folate levels. (e) Fruit phenotype at the mature-green (MG), breaker (BR), and red-ripe (RR) stages of ripening.…”
Section: Tf-5 Fruits Are Rich In Folate Contentmentioning
confidence: 99%
“…3.1 谷穗发育过程中叶酸合成途径关键基因表 达影响叶酸代谢物组成特征 谷子籽粒富含叶酸, 可作为人们日常摄入天然 叶酸的来源之一。深入探讨其籽粒中叶酸代谢谱分 布特征及相关基因表达模式, 为挖掘叶酸代谢关键 基因, 获得高稳定性叶酸材料, 培育高品质谷子品 种提供思路。Lian 等 [19] 在研究玉米籽粒发育过程叶 酸含量发现, 随着生育期的推进, 叶酸含量呈下降 趋势, 这与本研究中谷穗叶酸含量变化规律一致。 成熟小穗鲜样中所测得的叶酸总含量为 1.89 μg g 1 FW, 与本实验室测定干样含量存在差异(2.02 μg g 1 DW) [12] , 这是含水量差异所致。此外, 本研究仅用 含量降低的重要原因。Lian 等 [19] 对玉米籽粒中叶酸 含量的研究发现, 在未成熟籽粒中的 5-M-THF 的含 量高于成熟玉米籽, 进一步推测 5-M-THF 在穗发育 前期高含量可能是由于籽粒发育早期一碳循环更活 跃造成; Blancquaert 等 [21] 在水稻 pABA 含量上也观 察到类似的情况。除此之外, 叶酸介导所有生物必 需的一碳转移反应, 如 10-F-THF 和 5,10-CH=THF 衍生物的代谢参与嘌呤和胸苷酸的产生 [22] , SHMT1 通过参与羟甲基转移为生物合成提供一碳单位, 并 影响叶酸代谢; DHFR2 作为一碳途径和叶酸合成途 径的关键基因, 与叶酸主要化合物之间联系紧密。 在 拟南芥中, THF 合成的倒数第 2 个步骤是由双功能二 氢叶酸还原-胸苷酸合成酶(DHFR-TS)催完成 [23][24] 。在 这类双功能酶中, DHFR 酶位于 N 端, 将经过 TS 形 成的 DHF 还原为 THF [25] 。此外, 在本研究中发现, 物的生长发育过程中发挥重要的调控作用 [27] 。本研 究发现, 16 个叶酸合成关键基因发生了不同类型的可 变剪切, 且在穗发育不同时期可变剪切数目不同。 研究表明, IR 的发生可在转录本中插入提前终止密 码子, 使基因表达下调 [28] [33] 。叶酸在甲基化反应中提供 S-腺 苷蛋氨酸, 是甲基化反应的关键因素 [34] 。本研究发 现, 一碳代谢甲基化关键酶基因 DDM1、DDM2、 MET1、MET3 与叶酸合成基因 DHFR1、DHFR2 之 间有直接关系, 但叶酸代谢基因与甲基化相关基因 之间具体调控关系尚不明确。Wang 等 [35]…”
Section: 讨论unclassified